PENGARUH ELEMEN EKUITAS MEREK KESADARAN MEREK, ASOSIASI MEREK, PERSEPSI KUALITAS, DAN LOYALITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KOSMETIK WARDAH DI KOTA DEPOK - Ruminta, Darkiman; Khoirunnisa, Ayudya Feby; Wulandari, Dea (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study is entitled The Influence of Brand Equity Elements Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty on Consumer Purchasing Decisions of Wardah Cosmetics in Depok City. The purpose of this study was to determine the influence of brand equity elements of brand awareness, brand association, perceived quality, and brand loyalty on consumer purchasing decisions of Wardah cosmetics. The research method used in this study is a quantitative approach with data collection using a questionnaire with a total of 100 respondents who use Wardah brand cosmetic products. Data analysis using multiple linear regression and data processing with the JASP software application. The results of this study indicate that the brand awareness variable partially does not have a significant relationship to the purchase decision of Wardah cosmetics. The brand association variable also partially does not have a significant relationship to the purchase decision of Wardah cosmetics. The quality perception variable partially has a significant relationship to the purchase decision of Wardah cosmetics. The brand loyalty variable also partially shows no significant relationship to the dependent variable, namely the purchase decision. Simultaneously, the variables of brand awareness, brand association, perceived quality and brand loyalty together have a significant effect on the decision-making process for purchasing Wardah cosmetics.